A review on visual servoing for underwater vehicle manipulation systems automatic control and case study. (15th September 2022) - Huang, Hai; Bian, Xinyu; Cai, Fengchun; Li, Jiyong; Jiang, Tao; Zhang, Zhenkun; Sun, Chaoyu
Abstract: Visual servoing can greatly improve underwater robot manipulation accuracy and automation. Its main purpose is to control the end-effector pose of underwater vehicle manipulator systems (UVMS) relative to the target by using features extracted from image. However, underwater manipulation visual servoing suffers from the drawback of perception limitation of visibility range, obscure and low contrast image, inaccurate camera calibration and model parameters. This article has reviewed the state of major visual servoing method on UVMS including position based visual servoing (PBVS) and image based visual servoing (IBVS). On the problem of underwater manipulation and vision control, a novel hybrid strategy of visual servoing control based on uncalibrated visual servoing has been issued. Simulations and comparisons on PBVS, IBVS and proposed hybrid strategy have been made. The article is concluded with challenge analysis and future research trends discussions. Highlights: The major visual servoing method on UVMS including PBVS and IBVS have been systematically analyzed in detail. . A novel hybrid control strategy based on uncalibrated visual servoing has been issued, on the problem of underwater manipulation and vision control. Simulations are performed to verify the proposed method, which has contributed to the realization of high precision operations of UVMS for long distance.